2011
DOI: 10.1109/tii.2010.2085440
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the MAC Unreliability Problem in IEEE 802.15.4 Wireless Sensor Networks

Abstract: -Wireless Sensor Networks (WSNs) represent a very promising solution in the field of wireless technologies for industrial applications. However, for a credible deployment of WSNs in an industrial environment, four main properties need to be fulfilled, i.e., energy efficiency, scalability, reliability, and timeliness. In this paper we focus on IEEE 802.15.4 WSNs and show that they can suffer from a serious unreliability problem. This problem arises whenever the power management mechanism is enabled for energy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 32 publications
2
121
0
1
Order By: Relevance
“…The impact of the backoff exponent parameters (in particular macMinBE ) and payload size have been studied in [29,30] for IEEE 802.15.4 and Zigbee. Anastasi et al have investigated the effects of changing parameters like the packet arrival pattern (Poisson or periodic), the CSMA/CA parameters, beacon interval, packet size and different offered loads [31]. The impact of system parameters such as the packet arrival rate, number of stations, and packet size on the medium access probability or the queue length distribution is studied in [32] using Markov chain and queueing models.…”
Section: Related Workmentioning
confidence: 99%
“…The impact of the backoff exponent parameters (in particular macMinBE ) and payload size have been studied in [29,30] for IEEE 802.15.4 and Zigbee. Anastasi et al have investigated the effects of changing parameters like the packet arrival pattern (Poisson or periodic), the CSMA/CA parameters, beacon interval, packet size and different offered loads [31]. The impact of system parameters such as the packet arrival rate, number of stations, and packet size on the medium access probability or the queue length distribution is studied in [32] using Markov chain and queueing models.…”
Section: Related Workmentioning
confidence: 99%
“…In the context IEEE 802.15.4-based WSNs, many papers [12], [13], [14] highlighted that a significant share of transmitted messages may be lost due to contention, especially when the number of sensor nodes and the message size are large. In addition, [6] and [7] have shown that serious reliability issues arise when power management is enabled, even in networks with a small number of sensor nodes. It is also shown that a suitable setting of the MAC parameters can alleviate the problem, such that it is possible to achieve a target level of reliability, as well as a higher energy efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…It is also shown that a suitable setting of the MAC parameters can alleviate the problem, such that it is possible to achieve a target level of reliability, as well as a higher energy efficiency. However, [7], [6] are based on static (i.e., pre-defined) settings for the MAC parameters, hence they are not flexible enough to support dynamic operating conditions. In addition, a static parameter setting typically results in an energy consumption higher than necessary.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many communication protocols based on LEACH for WSN have been developed. The main research fields are energy efficiency, wireless link reliability [5], real-time capabilities [6], or quality-of-service. For the reason of sensor nodes just can use battery without power input.…”
Section: Introductionmentioning
confidence: 99%